Prevalence of Legal Liability in Sport Among Sports Council Personnel in South-South, Nigeria - Alaubi, Stanley C.; Deemua, G. A. (Advances in Social Sciences Research Journal, 2022)
This study is on the prevalence of legal liability in sports, among male athletes in sport councils in South-South Nigeria. Nine research questions and six null hypotheses were tested at 0.05 alpha levels. The population for this study comprised of all the 3,321 athletes and coaches in south south Nigeria with a sample size of 645 respondents (140 coaches and 505 athletes). The study adopted the cross sectional survey design. The sampling technique used was multi stage sampling procedure. The research instrument was subject to both face and content validation by the researcher’s supervisor and two experts in the field of measurement and evaluation. The reliability coefficient of 0.78 was obtained using the Pearson Product Moment Correlation statistical analysis. The collected data were analyzed using frequency, percentage, mean and standard deviation for the research questions, while multiple regression were used for the testing of the null hypotheses at 0.05 alpha level of significance. Prevalence of legal liability in sports is rare among Sports personnel in South-South Nigeria; 403 (62.3%) not being involved in prevalence, while only 242 (37.7%) experienced prevalence. Based on these findings, it was recommended among others that: Ministry of sport should introduce sporting activities, training and retraining from time to time in order to improve the knowledge of Sports personnel with issues relating to legal liability in sport.